Borderline Japan foreigners and frontier controls in the postwar era - Morris-Suzuki, Tessa (Cambridge University Press, 2010)
"This book offers a radical reinterpretation of postwar Japan's policies towards immigrants and foreign residents. Drawing on a wealth of historical material, Tessa Morris-Suzuki shows how the Cold War played a decisive role in shaping Japan's migration controls. She explores the little-known world of the thousands of Korean 'boat people' who entered Japan in the immediate postwar period, focuses attention on the US military service people and their families and employees, and also takes readers behind the walls of Japan's notorious Omura migrant detention centre, and into the lives of Koreans who opted to leave Japan in search of a better future in communist North Korea. This book offers a fascinating contrast to traditional images of postwar Japan and sheds new light on the origins and the dilemmas of migration policy in twenty-first century Japan"--Provided by publisher.